Combination of CDX2 H-score quantitative analysis with CD3 AI-guided analysis identifies patients with a good prognosis only in stage III colon cancer. (September 2022) - Derangère, Valentin; Lecuelle, Julie; Lepage, Come; Aoulad-Ben Salem, Oumaima; Allatessem, Ben M.; Ilie, Alis; Bouché, Olivier; Phelip, Jean-Marc; Baconnier, Mathieu; Pezet, Denis; Sebbagh, Virginie; Terrebonne, Eric; et al.
Abstract: Aim: Stratification of colon cancer (CC) of patients with stage II and III for risk of relapse is still needed especially to drive adjuvant therapy administration. Our study evaluates the prognostic performance of two known biomarkers, CDX2 and CD3, standalone or their combined information in stage II and III CC. Patients and methods: CDX2 and CD3 expression was evaluated in Prodige-13 study gathering 443 stage II and 398 stage III primary CC on whole slide colectomy. We developed for this study an H-score to quantify CDX2 expression and used our artificial intelligence (AI)-guided tissue analysis ColoClass to detect CD3 in tumour core and invasive margin. Association between biomarkers and relapse-free survival was investigated. Results: Univariate analysis showed that the combined variable CD3-TC and CD3-IM was associated with prognosis in both stage II and stage III. CDX2, on the contrary, was associated with prognosis only in stage III. We subsequently associated CDX2 and combined immune parameters only in stage III. This multivariate analysis allowed us to distinguish a proportion of stage III CC harbouring a high CDX2 expression and a high immune infiltration with a particularly good prognosis compared to their counterpart. Conclusion: This study validated the prognostic role of CDX2 and CD3 evaluated with immunohistochemistry procedures in stage III but not in stage II. This association would be conceivable in a routine pathology laboratory and could help oncologist to consider chemotherapy de-escalation for a part of stage III patients. Highlights: CDX2 H-score evaluation is a prognostic marker in stage III CC but not in stage II. CD3 IHC-automated evaluation by AI is prognostic in both stage II and stage III CC. Combination of CDX2 and CD3 selects stage III CC with a good prognosis. Combination could be used to consider chemotherapy de-escalation in stage III CC.